Gallery of Learning with Geogebra: Does it Affect Students’ Learning Motivation? - Putra, Aan; Hafis, M; Laswadi, Laswadi; Oktafia, Mesi (Indonesian Journal of Science and Mathematics Education, 2020)
This study aimed to determine the effect of Gallery of Learning with Geogebra as active learning strategies on students’ learning motivation. This research was a quantitative study with the one grup pretest-posttest design. The population of this study was all eight-grade students of SMP Negeri 27 Kerinci. The sample consisted of 27 students which selected by saturated sampling techniques. Student motivation data were obtained from motivation questionnaires that given before and after the application of the Gallery of Learning with Geogebra as active learning strategy. Data processing of student motivation was done by comparing students' motivation scores before and after treatmen by, using the t-test. The t-test results indicated that there was influence on the implementation of the active learning strategy of Gallery of Learning with Geogebra on students' learning motivation.